Uso y abusos señoriales en Castilla durante el siglo XVI: pleito entre el concejo de Villafáfila y el marqués de Távara - Granja Alonso, Manuel de la (Estudios humanísticos. Geografía, historia y arte, 1999)
The Marquis of Tábara, once he acquired Villafáfila manor and appurtenant properties, thought he had a right to use and abuse his new property as he deemed fit. The council and dwellers of the State opposed themselves to this conduct and brought an action against the Marquis before the Court of Chancery at Valladolid. The claimed that their custom and usage be respected as the forrner owners, the Comendadores of the Order of Santiago had done. The Court established thad there was case for the plaintiffs.